TCTEX1D2 is essential for sperm flagellum formation in mice - Ryua Harima; Kenshiro Hara; Kentaro Tanemura (Scientific Reports)
Abstract Flagella and cilia are widely conserved motile structures, in mammalian, sperm possess flagella. Large protein complexes called dynein, including cytoplasmic dynein 2 and axonemal dynein, play a role in the formation of cilia and flagella. The function of each subunit component of dynein complexes in sperm flagellum formation remains unclear. One such subunit is TCTEX1D2. Co-immunoprecipitation studies showed that TCTEX1D2 interacted with cytoplasmic dynein 2 subunits WDR34, WDR60, and DYNLT1 in the testes. Furthermore, TCTEX1D2 also interacted with WDR63 and WDR78, subunits of inner dynein arm, which is axonemal dynein. Tctex1d2 −/− mice generated in this study exhibited male infertility due to flagellar dysplasia, and the axonemal structures were disrupted inside the flagella. Further, the localization of cytoplasmic dynein 2 subunits was abnormal in in Tctex1d2 −/− mice. In contrast, the motile cilia of Tctex1d2 −/− mice were normal. Overall, we revealed that TCTEX1D2 is important for the assembly of cytoplasmic dynein 2 and inner dynein arm and functions in two distinct dynein complexes during mouse sperm flagellum formation. This is only in sperm flagellum formation, not in cilia formation.